Methylation status of MGMT and SPOCK2 in diffuse large B-cell lymphoma - Zainuddin, Norafiza; Mohd. Ridah, Lailatul Jalilah; Omar, Aqilah Nabihah; A. Talib, Norlelawati; Muhammad, Naznin; Hussain, Faezatul Arbaeyah (2016)
MGMT (O6-Methylguanine-DNA Methyltransferase) suppresses tumour development by removing alkyl adduct, while SPOCK2 (SPARC/Osteonectin CWCV and Kazal-like domains proteoglycan) abolishes the inhibition of membrane-type matrix metalloproteinases (MT-MMP) which leads to angiogenesis. Hence, MGMT methylation may initiate malignant cells transformation. In contrast, SPOCK2 methylation is hypothesized not to be a common event in diffuse large B-cell lymphoma (DLBCL). In this study, we examined the methylation status of MGMT and SPOCK2 in DLBCL as in Malaysia the information is extremely lacking. A total of 88 formalin-fixed paraffin-embedded tissue of patients diagnosed with DLBCL from the year 2006 to 2013 were retrieved from Hospital Universiti Sains Malaysia and Hospital Tengku Ampuan Afzan. Methylation-specific PCR (MSP) was used to examine the methylation status of both genes. Interestingly, methylation of MGMT was detected in all the 88 DLBCL samples, whereas SPOCK2 was found to be methylated in 83 of 88 (94.3%) DLBCL cases. Our study showed a remarkably high percentage of promoter methylation of both MGMT and SPOCK2 genes. Our finding also negates initial expectation that SPOCK2 methylation would be an uncommon event in the majority of DLBCL cases. This study has shown a very high percentage of promoter methylation of MGMT and SPOCK2 in the DLBCL cases studied by MSP, using archival lymphoma tissues. Nonetheless, additional research is needed to quantitatively evaluate MGMT and SPOCK2 methylation, and to analyse gene expression and/or protein expression in order to further understand the role of MGMT and SPOCK2 methylation in the pathogenesis of DLBCL.